Taurus of Beirut the other side of middle platonism - Petrucci, Federico M. 1985- (Issues in ancient philosophy, 2018)
This volume is the first monograph devoted to the philosophy of Taurus of Beirut, and provides a long-awaited analysis of his texts and their first English translation. Through close examination of the extant witnesses, Petrucci gives a new account of Middle Platonism based on a fresh approach to the theological and cosmological view of Taurus. In this way, the book contributes substantially to the debate on Post-Hellenistic Platonism from the point of view of both exegetical methods and philosophical doctrines, and offers a starting point for a new understanding of many aspects of ancient thought